A genetically inactivated two-component acellular pertussis vaccine, alone or combined with tetanus and reduced-dose diphtheria vaccines, in adolescents: a phase 2/3, randomised controlled non-inferiority trial. Issue 1 (January 2018) - Sricharoenchai, Sirintip; Sirivichayakul, Chukiat; Chokephaibulkit, Kulkanya; Pitisuttithum, Punnee; Dhitavat, Jittima; Pitisuthitham, Arom; Phongsamart, Wanatpreeya; Boonnak, Kobporn; Lapphra, Keswadee; Sabmee, Yupa; Wittawatmongkol, Orasri; Chinwangso, Pailinrut; et al.
Summary: Background: Increasing evidence shows that protection induced by acellular pertussis vaccines is short-lived, requiring repeated booster vaccination to control pertussis disease. We aimed to assess the safety and immunogenicity of a recombinant acellular pertussis vaccine containing genetically inactivated pertussis toxin and filamentous haemagglutinin, as either a monovalent vaccine (aP[PTgen/FHA] ) or in combination with tetanus and reduced-dose diphtheria vaccines (TdaP[PTgen/FHA] ), versus a licensed tetanus and reduced-dose diphtheria and acellular pertussis combination vaccine (Tdap). Methods: We did this phase 2/3, randomised controlled non-inferiority trial at two sites in Bangkok, Thailand. Healthy adolescents (aged 12–17 years) were randomly assigned (1:1:1), via a computer-generated randomisation list with block sizes of three, to receive one dose (0·5 mL) of aP(PTgen/FHA), TdaP(PTgen/FHA), or Tdap (comparator). Clinical research staff responsible for participant randomisation, vaccine preparation and administration, and accountability were aware of group allocation. However, allocation was concealed from all other site study staff, data management personnel, statisticians, laboratory staff, and study participants. The primary outcome was non-inferior immunogenicity of TdaP(PTgen/FHA) to Tdap based on seroconversion rates (a four-fold increase or more) for pertussis toxin and filamentous haemagglutinin IgG antibodies 28 days after vaccination, with a predefined 10% margin of equivalence. We did analysis by per protocol. This study is registered with the Thai Clinical Trial Registry, number TCTR20150703002. Findings: Between July 6 and Aug 20, 2015, we allocated 450 participants to receive one dose of TdaP(PTgen/FHA) (n=150), aP(PTgen/FHA) (n=150), or comparator Tdap (n=150). 28 days after vaccination, seroconversion rates for anti-pertussis toxin IgG were 96·6% (95% CI 93·8–99·5; n=144) in the TdaP(PTgen/FHA) group and 55·0% (47·1–63·0; n=82) in the comparator Tdap group (difference 41·6%, 95% CI 33·1–50·1; p<0·0001). Seroconversion rates for anti-filamentous haemagglutinin were 82·6% (95% CI 76·5–88·6; n=123) in the TdaP(PTgen/FHA) group and 54·4% (46·4–62·4; n=81) in the comparator group (difference 28·2%, 95% CI 18·1–38·2 p<0·0001). 28 days after vaccination, seroconversion rates in the aP(PTgen/FHA) group were 96·0% (95% CI 92·8–99·1; n=142) for anti-pertussis toxin IgG and 93·2% (89·2–97·3; n=138) for anti-filamentous haemagglutinin IgG. These findings support the non-inferior immunogenicity of TdaP(PTgen/FHA) over comparator Tdap. Reactogenicity and incidence of adverse events were similar between groups. Interpretation: The new TdaP(PTgen/FHA) vaccine is safe and induces higher pertussis responses 28 days after vaccination than does the available licensed Tdap booster vaccine. Results of our trial led to the licensure of new acellular pertussis vaccines containing genetically inactivated pertussis toxin in Thailand. The availability of recombinant monovalent pertussis vaccines that induce high antibody responses provides the medical community and consumers with the opportunity to vaccinate against pertussis when immunisation against diphtheria and tetanus is not required or not desired. Studies are underway to pave the way for licensure studies of this acellular pertussis vaccine in other countries. Funding: BioNet-Asia.